2015
DOI: 10.1007/978-3-662-48800-3_2
|View full text |Cite
|
Sign up to set email alerts
|

The Tower Number Field Sieve

Abstract: Abstract. The security of pairing-based crypto-systems relies on the difficulty to compute discrete logarithms in finite fields Fpn where n is a small integer larger than 1. The state-of-art algorithm is the number field sieve (NFS) together with its many variants. When p has a special form (SNFS), as in many pairings constructions, NFS has a faster variant due to Joux and Pierrot. We present a new NFS variant for SNFS computations, which is better for some cryptographically relevant cases, according to a prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…It is possible that including some of the ideas of [17] would speed up our implementation. Further work also includes studying the practical aspects of the tower NFS variants [4,21]; this would imply sieving in dimension at least 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that including some of the ideas of [17] would speed up our implementation. Further work also includes studying the practical aspects of the tower NFS variants [4,21]; this would imply sieving in dimension at least 4.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, if we want to optimize the number of relations found, we need to consider a variant of the NFS in a higher dimension, that is, relying on polynomials of degree greater than 1. Although the complexity fits in the L(1/3, c) class, these finite fields where higher-dimensional sieving is required are those for which the constant c is highest compared to other finite fields, despite recent advances [4,6,21,25].…”
Section: Introductionmentioning
confidence: 99%
“…Below we provide an overview of the TNFS algorithm. More detailed descriptions can be found in [24,6]. The TNFS algorithm applies to fields F Q where Q = p n , p is a prime and n = ηκ is a factorisation of n. Depending on the values of η and κ, several variants are obtained.…”
Section: Basics Of the Tower Number Field Sieve Algorithmmentioning
confidence: 99%
“…The algorithm has been analysed and extended in a recent work [BGK15], in which the authors coined the term tower number field sieve. In particular, it has been shown that it applies to the whole range of large characteristic fields, achieving the same complexity L( 1 3 , ( 64 9 ) 1/3 ) as the medium number field sieve of [JLSV06], while being practically advantageous for certain cases.…”
Section: The Medium Number Field Sievementioning
confidence: 99%